Relationship between participation in in-service training program and academic competences among sport science university lectures / Ali Ibrahim Ali Dawo - Ali Dawo, Ali Ibrahim (2015)
In-service training programs have emerged as an ideal training platform for lecturers in various universities to enhance their professional competencies. This becomes a necessity owing to the rapid advances that prompt the acquisition of knowledge to improve the lecturers' competencies especially in sports science. The purpose of this study lies in investigating the relationship between participation in in-service training programs and academic competencies among Sport Science Lecturers in Libya and Malaysia. The need for in-service training among lecturers based on their participation in in-service activities was based on participation in planning (PPL), participation in implementation (PIM) and participation in evaluation (PEV). The competencies of Lecturers place focus on the competencies in planning instruction (CPI), competencies in conducting instruction (Cf.I), competencies evaluating instruction (CEI) and competencies in facilitating student's growth (CFS). Previous studies were reviewed to support the arguments presented in this study using prominent theories such as the Perceptual Psychology Theory, Innovation Theory of planned behaviour (ITPB) and Contingency Theory. To achieve the objectives of this study, a quantitative study based on the survey questionnaire was used to collect primary data from 320 sports science lecturers within 11 Universities in Libya and Malaysia. Non-probability (purposive sampling) was used in this study for sampling selection. The results and findings were analysed using the Statistical Package Social Sciences (SPSS) and Analysis of Moment Structure (AMOS) Software. The final model goodness fit satisfactory explained the value of X2 == 498.637. The NFl, TLI and GFI were above O.90.The eleven (11) major hypothetical statements have some direct effects on selected variables such as CPI, CCI, CEI and CFS tested and they were significant at 0.00 level. Theoretically, this study inferred two mediating variables. Firstly, Cel fully mediated the relationship between CPI and Clil. Secondly, CEI partially mediated the relationship between CCI and CFS. The current study has indicated that the integration of in-service training programs among the sports science lecturers improved the levels of competency to facilitate student's growth. The results obtained in this study depict the increasing need that relates to planning, implementation and evaluation of in-service training programs as an ideal improvement pathway of lecturers' competency at various universities. This suggests that the sports science lecturers should pay more attention towards the participation in in-service training programs that aim at upgrading their respective professional competencies. The implementation of the results of this study in universities in Libya and Malaysia is set to enhance competencies of lecturers as well as student growth which are at the forefront of government educational policies.